The Students’ Critical Thinking Skill in Exploiting Covalent Bond Material - Danora, Yunita; Hendayana, Sumar; Supriatna, Asep (FKIP - Universitas Riau, 2020)
This study aims to analyze students' critical thinking skill in exploiting covalent bond material. The method applied in this study was descriptive qualitative with a case study approach. It was conducted at one of high schools in Bandung were the participants were the tenth grade students’. The instruments used for data collection were audio, video and observation sheets. The collected data were analyzed using Transcript Based Lesson Analysis (TBLA). The results indicated that three out of twelve indicators of critical thinking skill had been identified in learning covalent bonds. The three indicators are formulating questions, answering the “why” questions, and identifying differences. The low achievement of critical thinking indicators was due to the method used in teaching which is still informative or transferring knowledge from teacher to student (teacher-centered) without giving sufficient time for students to reflect the material presented, link it with prior knowledge, or apply it in real life situations.